2016
DOI: 10.1177/1744806916685570
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological property and chemical sensitivity of primary afferent neurons that innervate rat whisker hair follicles

Abstract: Whisker hair follicles are sensory organs that sense touch and perform tactile discrimination in animals, and they are sites where sensory impulses are initiated when whisker hairs touch an object. The sensory signals are then conveyed by whisker afferent fibers to the brain for sensory perception. Electrophysiological property and chemical sensitivity of whisker afferent fibers, important factors affecting whisker sensory processing, are largely not known. In the present study, we performed patch-clamp record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Studies have shown the presence of vesicular glutamate transporters in Merkel cells (Maksimovic et al . ) and expression of P2X receptors in whisker afferent neurons (Ikeda and Gu ). Furthermore, we have recently shown that 5‐HT receptors and P2X receptors are co‐expressed in the majority of large‐sized whisker afferent neurons of the rats (Ikeda and Gu ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the presence of vesicular glutamate transporters in Merkel cells (Maksimovic et al . ) and expression of P2X receptors in whisker afferent neurons (Ikeda and Gu ). Furthermore, we have recently shown that 5‐HT receptors and P2X receptors are co‐expressed in the majority of large‐sized whisker afferent neurons of the rats (Ikeda and Gu ).…”
Section: Discussionmentioning
confidence: 99%
“…) and expression of P2X receptors in whisker afferent neurons (Ikeda and Gu ). Furthermore, we have recently shown that 5‐HT receptors and P2X receptors are co‐expressed in the majority of large‐sized whisker afferent neurons of the rats (Ikeda and Gu ). The lack of effects on SA1 responses by glutamate, ATP, and other tested candidates may suggest that their receptors are not present at the postsynaptic sites in Aβ‐afferent terminals of Merkel discs.…”
Section: Discussionmentioning
confidence: 99%